ANALISIS TINGKAT KEBUGARAN JASMANI SISWA KELAS XI SEKOLAH MENENGAH ATAS NEGERI 8 KOTA PADANG - Mely Hasanah Lubis; Sepriadi; Aldo Naza Putra; Indri Wulandari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem addressed in this study is that the physical fitness level of Grade XI students at SMA Negeri 8 Padang has not yet been identified. This study aimed to determine the physical fitness level of Grade XI students at SMA Negeri 8 Padang. The research was conducted at SMA Negeri 8 Padang in May 2026. This study employed a quantitative research design using descriptive analysis. The population consisted of all Grade XI students of SMA Negeri 8 Padang, totaling 345 students, comprising 164 male students and 181 female students. The sample was selected using the proportional random sampling technique. A total of 10% of the male students and 10% of the female students were selected, resulting in a sample of 34 students, consisting of 16 male students and 18 female students. Data were collected using the Indonesian Student Fitness Test (Tes Kebugaran Siswa Indonesia/TKSI) Phase F for senior high school students, which includes the Hand-Eye Coordination Test, Hand Touch Reaction Test, T-Test, Vertical Jump Test, Dipping Test, and Multi-Stage Fitness Test. The results showed that the average physical fitness score of Grade XI students at SMA Negeri 8 Padang was 15.88. This result indicates that the physical fitness level of Grade XI students at SMA Negeri 8 Padang falls into the low category.